Reduced transpiration response to precipitation pulses precedes mortality in a piñon-juniper woodland subject to prolonged drought - Plaut, Jennifer A (The New phytologist, 2013)
© 2013 The Authors. New Phytologist © 2013 New Phytologist Trust.